Fusarium Wilt Resistance in Castor: An Overview of the Recent Advances and Future Strategies for Genetic Improvement - M. V. Nagesh Kumar; V. Gouri Shankar; V. Ramya; D. Vishnu Vardhan Reddy (International Journal of Economic Plants)
Castor is one of the important non-edible oilseeds with immense industrial and commercial values. The major castor producing countries in the world are India, Brazil, USSR and China. India is the world leader with regard to castor area (13.20 lakh ha), production (22.0 lakh tons) and productivity (1653 kg ha-1). In castor, to release any hybrid or variety at state or national level in India, the entry should be wilt-resistant, in addition to possessing excellent yield and yield-contributing characters. Wilt caused by Fusarium oxysporum f.sp. ricini  is the most important soil and seed borne disease of castor causing significant yield losses. In India, the disease is observed in all the castor growing regions of the country. The extent of yield loss depends on the stage at which plant wilts with the losses ranging from 77% at flowering to 63% at 90 days and 39% in later stages on secondary branches. To our knowledge, only few studies were carried out on inheritance of fusarium wilt resistance in castor and were inconclusive. To thoroughly characterize wilt resistance and to provide a better understanding of the differences among the genotypes with varying levels of resistance, an integrated approach focusing on quantifying the levels of F. o. f.sp. ricini colonization through fungal DNA quantification coupled with microscopic examination of resistance expression within the root tissues and visual evaluation of symptoms is necessary. This information will be valuable to the castor breeders interested in improving castor wilt resistance, because they can prioritize their efforts according to the type and level of resistance expression desired.